Effect of selected 8-hydroxyquinoline-2-carboxanilides on viability and sulfate metabolism of Desulfovibrio piger - Kushkevych, Ivan; Vítězová, Monika; Kos, Jiří; Kollár, Peter; Jampílek, Josef (Journal of Applied Biomedicine, 2018)
An increased number of sulfate-reducing bacteria is often isolated from faeces of patients with gastrointestinal diseases, which can be the cause of the development of bowel inflammation. Frequent use of antibiotics causes the resistance of intestinal microorganisms and ineffective treatment of these diseases. The antimicrobial activity and biological properties of the selected ring-substituted 8-hydroxyquinoline-2-carboxanilides against Desulfovibrio piger Vib-7 were studied. The addition of these compounds in the cultivation medium inhibited the bacterial growth and the process of sulfate reduction dose-dependently. A significant cytotoxic activity under the influence of ring-substituted 8-hydroxyquinoline-2-carboxanilides was determined. The strongest cytotoxic effect of the derivatives was observed for compounds 8-hydroxy-N-(3-methoxyphenyl)quinoline-2-carboxamide and 8-hydroxy-N-(3-trifluoromethylphenyl)quinoline-2-carboxamide that caused a low survival of D. piger Vib-7 in concentration 17 μM and high toxicity rates.
Keywords: vyvíjení léků; antibakteriální látky; Desulfovibrio; Desulfovibrio piger; idiopatické střevní záněty; bakteriologické techniky; Bacteria; Inflammatory Bowel Diseases; Bacteriological Techniques; Anti-Bacterial Agents; ulcerózní kolitida; redukce síranu; Drug Development; Hydroxyquinolines; 8-hydroxychinolin-2-karboxanilidy; mikrobiální viabilita; Colitis, Ulcerative; hydroxychinoliny; Microbial Viability